2009
DOI: 10.1088/1742-6596/157/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Application of quantum cascade laser absorption spectroscopy to studies of fluorocarbon molecules

Abstract: Abstract. The recent advent of quantum cascade lasers (QCLs) enables room-temperature mid-infrared spectrometer operation which is particularly favourable for industrial process monitoring and control, i.e. the detection of transient and stable molecular species. Conversely, fluorocarbon containing radio-frequency discharges are of special interest for plasma etching and deposition as well as for fundamental studies on gas phase and plasma surface reactions. The application of QCL absorption spectroscopy to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…For two of these intra pulse sweeps ( R 1 and R 2 ) spectral micro-windows were defined, namely A 1 , A 2 and A 3 ( Figure 5c ), for which effective cross sections could be determined. Although the spectral coverage of the micro-windows is different the σ eff <ν> values are in good agreement ( Figure 5a ) [ 58 ].…”
Section: Pulsed Qclsmentioning
confidence: 94%
See 2 more Smart Citations
“…For two of these intra pulse sweeps ( R 1 and R 2 ) spectral micro-windows were defined, namely A 1 , A 2 and A 3 ( Figure 5c ), for which effective cross sections could be determined. Although the spectral coverage of the micro-windows is different the σ eff <ν> values are in good agreement ( Figure 5a ) [ 58 ].…”
Section: Pulsed Qclsmentioning
confidence: 94%
“…The absorption spectra are commonly complex in nature and as a result, they lack any appearance of the rapid passage phenomena (see Figure 5 or [32,57,58]). It has been demonstrated that defining effective absorption cross sections σ eff within a spectral micro-window <ν> in both the inter or intra pulse method may also lead to an adequate calibration (case ii) [32,58]. Absolute values for σ eff are obtained from a measurement of the incident and transmitted intensity, I 0 and I , of a standardized gas sample of known number density n and absorption length L : nσitaliceff(ν)=1Lln(I0(ν)I(ν)).…”
Section: Pulsed Qclsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known, that σ ef f may have a strong temperature dependence, e. g. for CF 4 and C 3 F 8 [17]. Therefore, calibration is preferably carried out close to the experimental conditions to avoid inaccuracies due to line broadening and non-linear absorption effects, since σ ef f factors in such phenomena.…”
Section: Determination Of Molecular Number Densitiesmentioning
confidence: 99%
“…In addition, in the case of pulsed QCLs whose instrumental line widths are significant larger than typical for lead salt diode lasers, the resulting absorption spectra may become structureless as shown by Hempel et al, who compared both laser based spectroscopical techniques for the detection of BCl 3 [10] (a typical spectrum is given below in figure 7). It has been demonstrated that defining effective absorption cross sections σ ef f within a spectral micro-window ν may also lead to an adequate calibration [7,16,17]. Absolute values for σ ef f are obtained from a separate measurement of the incident and transmitted intensity, I 0 and I, for different gas samples of known number density N and absorption length l:…”
Section: Determination Of Molecular Number Densitiesmentioning
confidence: 99%